Rock inhibitors in Alzheimer’s disease - Zheng, Chao; Xia, Weiming; Zhang, Jianhua (Frontiers in Aging, 2025)
Alzheimer’s disease (AD) is the most common age-related neurodegenerative disease and cause of dementia. AD pathology primarily involves the formation of amyloid β (Aβ) plaques and neurofibrillary tangles containing hyperphosphorylated tau (p-tau). While Aβ targeted treatments have shown clinical promise, other aspects of AD pathology such as microgliosis, astrocytosis, synaptic loss, and hypometabolism may be viable targets for treatment. Among notable novel therapeutic approaches, the Ras homolog (Rho)-associated kinases (ROCKs) are being investigated as targets for AD treatment, based on the observations that ROCK1/2 levels are elevated in AD, and activation or inhibition of ROCKs changes dendritic/synaptic structures, protein aggregate accumulation, inflammation, and gliosis. This review will highlight key findings on the effects of ROCK inhibition in Aβ and ptau pathologies, as well as its effects on neuroinflammation, synaptic density, and potentially metabolism and bioenergetics.